2015
DOI: 10.1111/jcms.12333
|View full text |Cite
|
Sign up to set email alerts
|

Teaching (Dissident) Theory in Crisis European Union

Abstract: The ongoing multifaceted crisis in the EU is both a curse and a blessing for the teaching of theory in the context of EU studies. Such teaching has long posed a range of pedagogical challenges because of the complexity of the empirical object under investigation and the broad range of theoretical perspectives that have been deployed to pose questions in relation to that object. On the one hand, the current crisis and its multiple effects only serve to compound these difficulties by raising yet more questions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Rather than reifying and petrifying the field, EU studies and its students need to be aware of the rich diversity of disciplinary and theoretical perspectives on European integration. Our discussion of professionalization shows the problems that arise as the disciplinary mainstream of political science becomes dominant within EU studies, with single‐discipline textbook approaches leaving EU studies blindsided by crises (Parker, ). In contrast, opening EU studies to disciplinary diversity (including other humanities and social science perspectives) and cross‐paradigm theoretical viewpoints (including Marxist, postcolonial, poststructural, feminist and critical social theories) enriches both research and teaching, rendering both field and subject more robust (Manners and Whitman, ).…”
Section: Conclusion: a Different Europe Is Possiblementioning
confidence: 99%
“…Rather than reifying and petrifying the field, EU studies and its students need to be aware of the rich diversity of disciplinary and theoretical perspectives on European integration. Our discussion of professionalization shows the problems that arise as the disciplinary mainstream of political science becomes dominant within EU studies, with single‐discipline textbook approaches leaving EU studies blindsided by crises (Parker, ). In contrast, opening EU studies to disciplinary diversity (including other humanities and social science perspectives) and cross‐paradigm theoretical viewpoints (including Marxist, postcolonial, poststructural, feminist and critical social theories) enriches both research and teaching, rendering both field and subject more robust (Manners and Whitman, ).…”
Section: Conclusion: a Different Europe Is Possiblementioning
confidence: 99%
“…Against this backdrop, in a first step, this paper restates and updates an earlier argument, that 'peripheral', 'dissident' or 'critical' approaches (Manners and Whitman 2016) ought not -and cannot easily -be neglected in the classroom (Parker 2016). In particular, it is suggested that, in the current context, it makes little sense to narrate integration only in terms of a 'mainstream' history and theory, conceived as encompassing a range of approaches that adopt a broadly liberal and pro-market understanding of integration and the EU.…”
Section: Introductionmentioning
confidence: 72%
“…Its institutions are complex, its history is widely debated and debatable and the academic and theoretical concepts deployed in its study are forever multiplying, as are the range of disciplines interested in it as object of study. Cutting through this complexity in order to render the EU intelligible and digestible is a challenge for teachers of EU politics (see Parker 2016;Bijsmans and Versluis 2020). What we are able to cover in our teaching is, of course, always audience and context specific.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, at the occasion of the 50th anniversary of the University Association for Contemporary European Studies (UACES), David et al (2017) write that European Studies is characterised by, among other things, its close ties with one of its main objects of study, the European Union (EU), and, related to the latter, its events-driven scholarship. Accordingly, the recent economic and financial crises, the migration crisis, and Brexit have raised questions about the EU's future that are echoed in our teaching, in our students' interests, and in the professional world that our graduates will join after graduation (Hodson and Puetter 2018;Parker 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We need to pay more attention to 'critical and reflexive perspectives, rather than treating the EU as a ''neutral'' object of study' (Rittberger and Blauberger 2018: 437), as well as 'better come to grips with the disintegrative dynamics' (438; see also Hodson and Puetter 2018). Similarly, Manners and Rosamond (2018) and Parker (2016) also argue that a thorough comprehension of European developments requires a more critical and diversified approach.…”
Section: Introductionmentioning
confidence: 99%